Pengaruh Indeks Pembangunan Manusia (IPM) Terhadap Tingkat Partisipasi Angkatan Kerja (TPAK) di Bukittinggi - Fitra Ananda, Ilham; Widianita, Rika (Bertuah Jurnal Syariah dan Ekonomi Islam, 2023)
This study aims to analyze the effect of the Human Development Index (HDI) on the Labor Force Participation Rate (TPAK) in Bukittinggi City in 2021-2022. This study uses a quantitative approach with a simple linear regression analysis method, which utilizes data from 2014 to 2022 to identify the relationship between HDI and TPAK. The results of the study indicate the need for more integrated policies, such as the development of the creative and digital economy sectors, skills training that is in accordance with market needs, and improving digital infrastructure. With an inclusive development strategy, it is hoped that labor force participation can increase along with improvements in the HDI, creating sustainable economic development in Bukittinggi City.